2022
DOI: 10.3390/app12136363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cognitive Task Difficulty in Postural Control and Hemodynamic Response in the Prefrontal Cortex during Static Postural Standing

Abstract: In daily life, we perform several tasks simultaneously, and it is essential to have adequate postural control to succeed. Furthermore, when performing two or more tasks concurrently, changes in postural oscillation are expected due to the competition for the attentional resources. The aim of this study was to evaluate and compare the center of pressure (CoP) behavior and the hemodynamic response of the prefrontal cortex during static postural standing while performing cognitive tasks of increasing levels of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Thus, during the cognitive dual-task, brain regions needed to recruit more cognitive resources to perform the task than in the motor dual-task, due to greater cognitive effort and the prefrontal cortex’s role in executive function. Some studies using neuroimaging techniques showed higher frontal lobe activity when subjects performed cognitive tasks compared with motor tasks [ 44 ]; others showed an increase in prefrontal cortex activity when performing a cognitive dual-task compared with a single task [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, during the cognitive dual-task, brain regions needed to recruit more cognitive resources to perform the task than in the motor dual-task, due to greater cognitive effort and the prefrontal cortex’s role in executive function. Some studies using neuroimaging techniques showed higher frontal lobe activity when subjects performed cognitive tasks compared with motor tasks [ 44 ]; others showed an increase in prefrontal cortex activity when performing a cognitive dual-task compared with a single task [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%